Blood Culture–Negative Cardiovascular Infection in a Patient With Multiple Sclerosis. (4th October 2019) - Melenotte, Cléa; Loukil, Ahmed; Rico, Audrey; Lepidi, Hubert; Raoult, Didier
Abstract: A patient with multiple sclerosis presented with seronegative C. burnetii endocarditis diagnosed using C. burnetii –specific polymerase chain reaction and fluorescence in situ hybridization on cardiovascular biopsy. This case supports the necessity of a systematic polymerase chain reaction testing of removed cardiac valves because blood culture–negative endocarditis can be pauci-symptomatic, and serological tests can be negative in cases of immunosuppression.